Experimental Test of Harmony Search Algorithm with Thousands of Dimensions - Vilca Apaza F. (2018)
Harmony Search Algorithm is a mimetic algorithm inspired on the process of musicians to create one harmony. It has been tested in many theoretical and real problems with good results. The objective of this work is to test the evolutionary algorithm with classical n-dimensional benchmark functions (Ackley, Schwefel) with a dimensionality of thousands to analyze the behaviour in this context. The results have showed the limitation of this metaheuristic with problems of higher dimensionality.